Hepatitis C in drug addicts: access and treatment compliance. - Sarmento E Castro, Rui (2011)
Currently, hepatitis C is a serious public health problem. It is estimated that there are 180 million people with chronic infection by hepatitis C virus (HCV) worldwide and that the prevalence of this infection in the Portuguese population ranges between 1 and 1.5%. In Portugal, there are neither up-to-date guidelines for treatment, nor recommendations for the diagnosis and management of patients with HCV and, in particular, for the endovenous drug users. The present article gathers consensus information regarding clinical practice and suggests some guidelines to the management and treatment accessibility of drug addicted patients with chronic infection by HCV, in Portugal.